2003
DOI: 10.1016/s1470-0328(03)03907-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality: only 42 days?

Abstract: Where living conditions are harsh, pregnancy and delivery affect the health of the woman for more than 42 days. Using the WHO definition may result in an under-estimation of the pregnancy-related part of the reproductive age mortality. Extending the definition of maternal death to include all deaths within three months of delivery may increase current estimates of maternal mortality by 10-15%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…This change in definition is important since there is evidence that risk of death is increased for up to 6 months postpartum. 2 In our study there were 10 cases of late maternal deaths, the longest case died 116 days after delivery due to brain stem hemorrhage resulted from eclamptic fits.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This change in definition is important since there is evidence that risk of death is increased for up to 6 months postpartum. 2 In our study there were 10 cases of late maternal deaths, the longest case died 116 days after delivery due to brain stem hemorrhage resulted from eclamptic fits.…”
Section: Discussionmentioning
confidence: 59%
“…1 The 42-day limit is somewhat arbitrary, and in recognizing the fact that modern life-sustaining procedures and technologies can delay death, ICD-10 introduced a new category, namely the late maternal death, which is defined as the death of a woman out of direct or indirect obstetric causes more than 42 days but less than one year after the termination of pregnancy. 2 Maternal mortality ratio is defined as the number of women who died while pregnant or within 42 days of termination of pregnancy per 100,000 live births. 3 Maternal deaths are divided into two groups.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal mortality surveillance studies such as confidential enquiry have showed that late maternal death is non-trivial in even low-resource settings34,59 and can account for up to 40% of maternal deaths in high-income settings 60. A contemporary linkage study in Mexico found that 18% of maternal deaths are missed when the definition is truncated at 42 days’ post partum 61.…”
Section: Discussionmentioning
confidence: 99%
“…30 Consequently, the contribution of pregnancy-related deaths to mortality among women of reproductive age is likely to be underestimated. Indeed, extending the definition to include all deaths within 3 months of delivery increases current estimates of maternal mortality in low-income settings by 10% to 15%.…”
Section: Researchmentioning
confidence: 99%
“…Indeed, extending the definition to include all deaths within 3 months of delivery increases current estimates of maternal mortality in low-income settings by 10% to 15%. [30][31][32] Incorporating late maternal deaths within 1 year of the end of pregnancy would further increase the figure.…”
Section: Researchmentioning
confidence: 99%